1994
DOI: 10.1002/ajhb.1310060509
|View full text |Cite
|
Sign up to set email alerts
|

Upper limit of fat‐free mass in humans: A study on Japanese Sumo wrestlers

Abstract: If limitations exist in skeletal dimensions, fat-free mass (FFM) might have an upper limit. To explore the upper limit to FFM, 37 professional Japanese Sumo wrestlers, 14 highly trained bodybuilders, and 26 untrained men were investigated for body composition (fat mass and FFM) and cross-sectional areas (CSA) of limb muscles, by hydrodensitometry and ultrasound, respectively. Mean % fat of Sumo wrestlers, bodybuilders, and untrained subjects were, respectively, 26.1%, 10.9%, and 12.1%. Sumo wrestlers had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 14 publications
1
35
2
Order By: Relevance
“…However, the trunk contains about one-half of all the body mass and lean tissue mass (Organ et al 1994). From the findings of Kondo et al (1994), who investigated the relationship between LBM and limb muscle CSA, as LBM increases, muscle CSA also increases, but a further increase in CSA is not apparent in LBM above 80 kg. This finding implies that an increase in LBM above 80 kg largely depends on the hypertrophy of lean tissues involved in the trunk.…”
Section: Discussionmentioning
confidence: 97%
“…However, the trunk contains about one-half of all the body mass and lean tissue mass (Organ et al 1994). From the findings of Kondo et al (1994), who investigated the relationship between LBM and limb muscle CSA, as LBM increases, muscle CSA also increases, but a further increase in CSA is not apparent in LBM above 80 kg. This finding implies that an increase in LBM above 80 kg largely depends on the hypertrophy of lean tissues involved in the trunk.…”
Section: Discussionmentioning
confidence: 97%
“…Based on a sample of healthy humans, it has been suggested that the upper limit of FFM accumulation in humans is about 100 kg (Forbes 1987a). However, several reports using athletes have observed greater FFM accumulation in American football players and sumo wrestlers (Wilmore et al 1976;Kondo et al 1994;Abe et al 1999). In the present study, two superheavy class lifters had over 110 kg FFM.…”
Section: Ffm Accumulation and Powerlifting Performancementioning
confidence: 95%
“…Underwater weighing was conducted according to the procedure described by Kondo et al (1984). Residual lung volume was measured by the closed-circuit oxygen dilution technique (Rahn et al 1949) whereby the subject sat in a position similar to that used during the underwater weighing procedure.…”
Section: Measurement Of Body Densitymentioning
confidence: 99%